If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = p(1 + -1p) x = (1 * p + -1p * p) x = (1p + -1p2) Solving x = 1p + -1p2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = 1p + -1p2
| 6y+7=-33-4y | | 4(3x-8)+16=2 | | 76=-v+249 | | 6=-4y+2(y+4) | | 10+3y=y+6 | | 3m+6=10m | | 2=44-x | | 4(3x-8)+16=12 | | 5y-1=12y-29 | | -7x+3y=9 | | 3.14(r)2*7= | | 6y+29=16y-91 | | 10x^2-9=449 | | 4y^2+23y+15=0 | | (b+8)(6-2b)= | | 4x-5=14-3x | | 3y-6=y+2 | | (-2x-4)(8x+3)= | | 3=-3y+36 | | 9(x+10)+3=5(1+x) | | 3=-3y+26 | | 9=8/4x | | 10(6n-9)=10(4-7n) | | -5=6x-1+2 | | -4(k-3)+6=-3k-16 | | h/2=13 | | 10=1-3x+6 | | 6(z+2)=28+2z | | 12=6n-4+2n | | 7(6+a)=6(2+a) | | -3-n=-5 | | -3d+4=-3+4d |